2017
DOI: 10.1007/s00268-017-4271-5
|View full text |Cite
|
Sign up to set email alerts
|

Safe Surgery for All: Early Lessons from Implementing a National Government‐Driven Surgical Plan in Ethiopia

Abstract: Recognizing the unmet need for surgical care in Ethiopia, the Federal Ministry of Health (FMOH) has pioneered innovative methodologies for surgical system development with Saving Lives through Safe Surgery (SaLTS). SaLTS is a national flagship initiative designed to improve access to safe, essential and emergency surgical and anaesthesia care across all levels of the healthcare system. Sustained commitment from the FMOH and their recruitment of implementing partners has led to notable accomplishments across th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
92
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(101 citation statements)
references
References 3 publications
1
92
0
2
Order By: Relevance
“…Baseline assessment for Zambia's NSOAP led to plans to increase its workforce from 1·1 to 3 surgery, obstetrics and anaesthesia providers per 100 000 population by 2021. In Ethiopia, a national Surgical Workforce Expansion Plan and Anaesthesia Roadmap was developed in close partnership with the College of Surgeons of East, Central and Southern Africa to address training of specialists, continuing education and task‐shifting programmes.…”
Section: Sdg 3: Healthy Lives and Well‐beingmentioning
confidence: 99%
See 2 more Smart Citations
“…Baseline assessment for Zambia's NSOAP led to plans to increase its workforce from 1·1 to 3 surgery, obstetrics and anaesthesia providers per 100 000 population by 2021. In Ethiopia, a national Surgical Workforce Expansion Plan and Anaesthesia Roadmap was developed in close partnership with the College of Surgeons of East, Central and Southern Africa to address training of specialists, continuing education and task‐shifting programmes.…”
Section: Sdg 3: Healthy Lives and Well‐beingmentioning
confidence: 99%
“…Ethiopia's baseline data collection revealed that, of the surgical facilities assessed, 72 per cent consistently lacked running water, 59 per cent had intermittent electricity and 33 per cent did not have a reliable oxygen supply. To address these gaps, the Ministry of Health allocated a budget for the construction and renovation of 370 operating rooms, and partnered with Safe Surgery 2020 to construct new oxygen plants. The development of a NSOAP for the expansion of surgical services is an innovative approach to surgical care, as it fosters local advances and opens new markets to promote the expansion of industry.…”
Section: Sdg 9: Industry Innovation and Infrastructurementioning
confidence: 99%
See 1 more Smart Citation
“…Two broad areas of focus for improving financing of surgical systems in Tanzania include increasing financial resource allocation to SOA care and implementing strategies to reduce catastrophic and impoverishing expenditure Procedures done in an operating theatre, per 100,000 population per year; 2 number of specialists surgical, anaesthesia, obstetric physicians who are working, per 100,000 population; 3 proportion of the population that can access, within 2 h, a facility that can do the Bellwether procedures; 4 proportion of households protected against catastrophic expenditure from direct out-of-pocket payments for surgical and anaesthesia care; 5 proportion of households protected against impoverishment from direct out-of-pocket payments for surgical and anaesthesia care; 6 all-cause death rate prior to discharge among patients who have undergone a procedure in an operating theatre, divided by the total number of procedures World J Surg (2019) 43: 24-35 31 to patients. Accordingly, the NSOAP finance section prioritizes the tracking of national budgetary allocations to surgical services including systemic and direct costs for providing surgical care as part of the national health account.…”
Section: Financingmentioning
confidence: 99%
“…Led by efforts at the World Health Organization (WHO), the scale up to 44 basic surgeries and safe anesthesia is underway, and in fact two Africa countries have proposed national surgical plans for the process [5,6]. As proposed by the Lancet Commission on Global Surgery and the WHO, this is an opportunity for tracking and improving outcomes, and initiating quality programs early in the scale up processes.…”
mentioning
confidence: 99%